A new high temperature, high heating rate, low axial gradient capillary heater - Kenneth P. Marshall; Hermann Emerich; Charles J. McMonagle; Chloe A. Fuller; Vadim Dyadkin; Dmitry Chernyshov; Wouter van Beek (Journal of Synchrotron Radiation, 2023)
A new heater design, capable of fast heating and cooling to and from >1000°C, has been developed at the Swiss–Norwegian Beamlines, European Synchrotron Radiation Facility, France. The design uses a SiC head to distribute heat, and resistive Si3N4 heat cartridges to provide heat.